Melacak Makna “Dain” dalam Al-Quran Perspektif Analisis Semantik Toshihiko Izutsu dan Penerapannya dalam Platform Belanja Online - Mohammad Zainal Hamdy; Riski Gunawan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
In Islamic teachings, debt (Dain) is a permissible transaction, but it is mandatory to be careful in implementing and carrying it out so as not to fall into something that is prohibited by Islam, namely Riba. Researchers will examine and trace the concept of Dain in the Qur'an using Toshihiko Izutsu's semantic analysis. In addition, the concept of Dain in the Qur'an has it been implemented correctly in several online shopping platforms that implement loans or debts such as Shopee and Lazada. researchers use a qualitative approach and the method or type of research used by researchers is Library Research. The results show that in the Qur'an, the concept of